Analisis CSR Terhadap Kinerja Perusahaan - Kholis, Nur (Graduasi: Jurnal Bisnis & Ekonomi, 2015)
Purpose of this study  was to obtain empirical evidence that Corporate Social Responsibility  (  CSR  ) has  an  influence  on  the  corporate  performance  in  showed  with ROA (Return on Assets ) and ROE (Return on Equity ). This study used secondary data obtained from the companys annual report, published in the Stock Exchange s website and the official website of the company. Techniques used in sampling in this research is using purposive sampling method .   Based  on  the  results  of  the  study  founding  that  the  variables  of  Corporate Social  Responsibility  (  CSR  ) significant  difference between Corporate Social Responsibility  (  CSR  ) on the financial performance  in  showed  with  Return  on  Assets  ( ROA ), Return on Equity ( ROE ) .